Conjugation of nanomaterials containing rare-earth ion Tb3+ with CD133 monoclonal antibody and its potentials for labeling colon cancer cells (HT-29) - Nhat Minh, Le; Trong Nhan, Vo; Thi Nga, Nguyen; Thu Huong, Tran; Thi Kim Hue, Phung; Thi Thao, Do (Vietnam Journal of Biotechnology, 2020)
Nanotechnology is the key technology that brings many important applications in biomedical research.Nanolantanites present high stability, easy fabrication and functionalization. Tb3+ ion-containing nanomaterial, a specific type of nanolantanites, possess great prospects. In addition, cancer stem cells (CSCs) are directlyrelated to drug resistance, metastasis, recurrent cancer, etc. Therefore, CSCs are considered as the target forcancer researching and for discovery of more effective therapies. CD133, a trans-membrane glycoprotein, isone of the typical markers that are found to appear very commonly on the surface of many types of CSCs. Inthis study, CD133 monoclonal antibody (MAb) was cojugated with nanomaterials containing Tb3+. Thecoupling between fluorescented nanomaterials containing Tb3+ ions and CD133 MAb was then incubated withhuman colon cancer cells (HT-29) to evaluate its ability to label CSCs in vitro. The results showed thatnanorods containing rare-earth based Tb3+ ions which were fabricated by hydrothermal method, present thelength of about 300 - 800 nm and the diameter in range of 40 - 50 nm. The Tb3+ nanoparticals also havehexagonal structure of terbium phosphate monohydrate and green illuminant. Tb3+ nanorods were also furthersurface silica coated and amino-silane functionalized. This nanostructure was successfully combined withmonoclonal antibodies against CD133 which labelled the surface marker of HT-29 human colon cancer cells.As a result, the combination of CD133+TbPO4@Silica-NH2 (functionalized surface) showed strongerluminescence than the CD133+TbPO4 unfunctionalized combination.